New forces at work : industry views critical technologies - Popper, Steven W., 1953- (MR (Rand Corporation), 1998)
For the fourth in a series of inquiries into the state of critical technologies in the United States, the Office of Science and Technology Policy in the Executive Office of the President asked a RAND Critical Technologies Institute research team to engage business and industry leaders explicitly in a discussion of the issue of critical technologies by gathering private-sector views on what technologies are appropriate to consider under this rubric--and why. The primary substantive input was elicited through extended, detailed interviews conducted individually, usually with one firm's senior executive per session, on-site in most cases. This report presents an analysis of the information gained during the course of those interviews. The report presents and analyzes interviewees' responses to what technologies they consider to be critical to their firm or industry; explores the question of what "critical technology" means; reports interviewees' assessments of the status of U.S.